Who steals?: wo bribes? : multilevel determinants of corruption types in China - Li, Hui (Crime, law and social change, 2023)
Numerous studies have pointed out that as the political and economic environment changes, the structures of corruption in China are constantly evolving. Specifically, the transaction-type corruption has surged and the auto-corruption ( non-transactional administrative corruption) has receded. As such, what kind of structural characteristics does China’s corruption types present today? What factors can help us explain the variances of these structural characteristics? Drawn on the quantitative analysis of a novel dataset, this study found that: in terms of personal traits, the gender of the defendant and urban-rural residence have a significant impact on the type of corruption; in the macro-institutional environment, the development of private economy and the size of the government have opposite effects on the composition of the corruption type. Privatization increases the probability of transaction-type corruption. The size of the government increases the probability of auto-corruption.